Desenvolvimento de um sistema de detecção de quedas para idosos - Silva, Eujessika Katielly Rodrigues (2018)
Elderly people falling on the ground has called big interest in the public health care field due to demanding costs needed to the care about the sequels coming out from these facts, besides the fact that they present high rate of mortality in the elderly population. The body unbalance is one of the most relevant complains in the process of human aging, thus leading to a higher probability to elderly people falling down. Despite of being more subject to risks, studies show that elderly people tend to prefer to stay in their own houses, whether with the companionship of their relatives or not. This way, there is a need to create monitoring measures in order to help in the identification of falling occurrences of the elderly. During the event of the falling, the body takes a speed variation until it gets to have the impact to the ground, this variation of speed may be measured through a wireless sensor, the accelerometer. Therefore, we have created a detecting system for the possible events of falling with the elderly. Considering the researches advance and good adhesion of the wearable technologies, we have developed the system in order to be used in a smartwatch already available in the market. The smartwatch is able to identify all the event of the falling through an algorithm developed by the researchers, as well as presenting the function to click a bottom in case of emergency. The smartwatch communicates with the care taker of the elderly, sending the information obtained by the sensor to the mobile app of the caretaker‟s smartphone. The mobile app, as soon as receiving the alert, provides the phone call to the elderly or the local emergency assistance that is previously registered, this way leading to a decrease of time in the adequate assistance, and therefore less sequels and complications from the occurrences of falling. The mobile app has also the possibility to register some information about the elderly with the aim to provide an overview of the general profile of the system users and their involvement with the falling. Therefore, the developed system is able to identify the occurrences of falling involving the elderly person, through a wearable technology, being minimally evasive, thus making the constant monitoring of its user possible.